Efeito do eCG ou benzoato de estradiol associado ao norgestomet na taxa de concepção de vacas de corte submetidas à IATF no pós-parto - Rossa, Luis Augusto Ferreira; Bertan, Claudia Maria [UNESP]; de Almeida, Alexandre Barreto; Gaspar, Pércio dos Santos; Mazza, Paulo Henrique; Binelli, Mario; Baruselli, Pietro Sampaio; Madureira, Ed Hoffmann (My University, 2009)
This study aimed to compare conception rates at the postpartum period (PPP) in beef cows which were administered either Equine Chorionic Gonadotrophin (eCG) or Estradiol Benzoate (EB) after Norgestomet and submitted to fixed-time artificial insemination (FTAI). The hypothesis was that the administration of eCG or EB enhances the conception rate. Lactating Nelore cows (n=138) and Brangus (n = 63), between 26 and 118 days of post partum period (PPP) were divided into three homogeneous groups, and subdivided in two blocks, inside each group one of them with a PPP d'' 45 days (PPP1; n=107) and another with a PPP > 45 days (PPP2; n=94). All cows received an auricular implant containing 3mg Norgestomet (Crestar®), followed by the administration of 5mg Estradiol Valerate. The auricular implants were kept during 10 days. Cows received 1mL saline solution (n=68, Control Group) or 500IU eCG (Folligon®; n=67; eCG Group) or 1mg Estradiol Benzoate (Index, n=66; EB Group) 24 hours after the removal of the implant. FTAI was made 54 hours after the implant removal. The pregnancy diagnosis was carried through ultrasonography 30 days after FTAI. There was an interaction between treatments and PPP. In the PPP1, the conception rate was higher in the eCG Group than in the EB Group (47.22% vs. 15.38%; Pd''0.01). In the PPP2, the conception rates of the eCG and EB Groups were higher than in the Control Group (41.93%, 44.44% vs. 22.22%: Pd''0.01). It was concluded that in cows up to 45 days of PPP, the eCG associated with Norgestomet enhances the conception rates.
Effect of eCG or estradiol benzoate associated with norgestomet on the conception rate of beef cows submitted to FTAI in the postpartum
Keywords: Cows; eCG; Estradiol benzoate; Norgestomet; Postpartum; Equidae